IL-33 AS A BIOMARKER OF INFLAMMATORY ACTIVITY IN PSORIASIS PATIENTS WITH CONCOMITANT OBESITY - Yemchenko, Ya.O.; Ischeikin, K.Ye.; Kaidashev, I.P.; Izmailova, O.V. (World of Medicine and Biology, 2021)
Recently, there has been an increase in cases of comorbid psoriasis and obesity, which leads to severe, atypical, disabling, and therapy - resistant forms of dermatosis which form a vicious circle at the level of the immune system, which must be broken in order to treat these diseases successfully. In this study, we examined the serum IL-33 level and its association with rates of systemic inflammation, the severity of psoriasis and obesity. We applied the enzyme immunoassay to evaluate the severity of systemic inflammation. We determined the concentration of IL-33, interleukin-6, and high sensitivity C-reactive protein in the serum. PASI was used to assess the severity of psoriasis. We used BMI to determine the extent of alimentary obesity. There was a positive statistically significant correlation between the serum IL-33 concentration, the severity of psoriasis, the level of systemic inflammation, and the degree of alimentary obesity.
Keywords: psoriasis; alimentary obesity; IL-33; clinic